Binge Eating and Addictive-Like Behaviours in Males and Females. Issue 1 (February 2022) - Levallius, Johanna; Monell, Elin; Birgegård, Andreas; Clinton, David; Forsén Mantilla, Emma
Introduction: Binge eating is a common behaviour that is strongly linked to both obesity and eating disorder. There is evidence that binge eating commonly co-occurs with other problematic and addictive-like behaviours; however, this has not been explored systematically. The present study aimed to examine the relationship between binge eating, body weight, disordered eating behaviours and associated addictive-like behaviours, with particular attention paid to gender differences. Method: A community sample ( N = 500; 75% female, Mage = 32.5 years) reported disordered eating behaviours (i.e. binge eating, purging, restriction of eating, compulsive exercise), body mass index (BMI), food addiction, starvation addiction, exercise dependence, tobacco use and alcohol consumption. Results: 42% of females and 21% of males reported binge eating during the past four weeks. Binge eating was significantly associated with all investigated behaviours in females, and with purging, compulsive exercise and overweight/obesity in males. Controlling for BMI, self-starvation predicted binge eating in males (OR = 1.07), while food addiction (OR = 1.73) and alcohol dependence (OR = 1.11) predicted binge eating in females. Conclusions: The multiple associations between binge eating and addictive-like behaviors supports broad screening and generalized prevention efforts. Prevention efforts should reflect gender differences.